1999
DOI: 10.1046/j.1365-2559.1999.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Cystic partially differentiated nephroblastoma in an adult: an immunohistochemical, lectin histochemical and ultrastructural study

Abstract: CPDN does occur in adults, as experienced in Wilms' tumour, though its incidence is extremely low. This study suggests that CPDN may show maturation intermediate between cystic nephroma and Wilms' tumour, even in adult cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…A hobnail pattern is described in a wide range of tumors from different organs, including ovary 12 in which it is associated with both benign and malignant lesions. 7,15,18 In thyroid neoplasms, the loss of the cellular polarity/cohesiveness and hobnail features was first described in PTC by Tang et al 22 who found a correlation with retinoid receptor expression. Kakudo et al 11 suggested that they were useful parameters for identifying a distinctive group in common type PTC and in predicting patient's outcome in terms of tumor recurrence and cancer related death.…”
Section: Discussionmentioning
confidence: 98%
“…A hobnail pattern is described in a wide range of tumors from different organs, including ovary 12 in which it is associated with both benign and malignant lesions. 7,15,18 In thyroid neoplasms, the loss of the cellular polarity/cohesiveness and hobnail features was first described in PTC by Tang et al 22 who found a correlation with retinoid receptor expression. Kakudo et al 11 suggested that they were useful parameters for identifying a distinctive group in common type PTC and in predicting patient's outcome in terms of tumor recurrence and cancer related death.…”
Section: Discussionmentioning
confidence: 98%
“…Due to this criterion, the diagnosis of cystic partially differentiated nephroblastoma can be excluded in an adult patient with a renal neoplasm. In the literature we found an extremely rare case of this tumour reported in an adult [27,28]. The lesion is benign [1].…”
Section: Cystic Partially Differentiated Nephroblastomamentioning
confidence: 99%
“…3,4 This entity of tumours with similar morphologic findings had been previously described under various diagnoses, such as adult type mesoblastic nephroma, 5-8 cystic hamartoma of the renal pelvis, 9,10 cystic nephroma 11 or mature nephroblastic nephroma and cystic partially differentiated nephroblastoma. 12,13 Of the 100 reported cases of MEST in the literature, there are only 8 cases of men, including our case. [14][15][16] There is a possible hormonal pathogenetic mechanism involved in MEST -most female perimenopausal patients take longterm estrogen replacement therapy and the men with MEST have a history of hormone therapy.…”
Section: Discussionmentioning
confidence: 78%